Identifying and prioritizing the main strategies of the Army in order to realize the vision of the strategic statement of the second step of the Islamic Revolution - Mohhamad Abasiyan; Alireza Mirjomehri; Mahdi Pourseifi (آینده‌پژوهی دفاعی, 2023)
The aim of this study was to "identify and prioritize NEZAJA’s strategies in order to achieve the vision of the statement of the second step of the Revolution". The type of research is applied and descriptive-survey method. NEZAJA’s scientific-military experts are the present study population and statistical samples including 53 of them were selected by purposive sampling. First, by holding expert meetings regarding the analysis of the second step statement of the Revolution, 10 new strategies of NEZAJA were identified. Then, using the data collection tool (prioritization questionnaire), the identified strategies were prioritized. The validity of the questionnaire was confirmed based on the opinion of experts and its reliability was obtained based on Cronbach's alpha of %90.2. LISREL was used to fit the model and descriptive and inferential statistical indices were used to analyze the data using SPSS. The results show that the degree of prioritization of NEZAJA's ten strategies in order to achieve the vision of the declaration of the second step of the revolution is generally in a "priority". The prioritization of the identified ten strategies also showed that the strategies of "developing motivational subsystems" (with a mean and standard deviation: 3.92±1.412), "Improving combat readiness by developing technologies Modern UAVs, ground combat and war game systems "(3.75±1.440) and also" Establishment of a system for talent identification and elite defense of human resources" (3.72±1.350) have the highest priority for achieving the vision of the declaration of the second step of the revolution.